2011
DOI: 10.1016/j.bbcan.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal influence on tumor progression

Abstract: Nerve fibers accompany blood and lymphatic vessels all over the body. An extensive amount of knowledge has been obtained with regard to tumor angiogenesis and tumor lymphangiogenesis, yet little is known about the potential biological effects of "neoneurogenesis". Cancer cells can exploit the advantage of the factors released by the nerve fibers to generate a positive microenvironment for cell survival and proliferation. At the same time, they can stimulate the formation of neurites by secreting neurotrophic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
126
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 223 publications
1
126
0
Order By: Relevance
“…These types of events occur due to secretion of catecholamines (stress-mediators) which increases in response to stressful events (Ganguly, 2010;Beaulieu and Gainetdinov, 2011). Most of catecholamines including epinephrine and norepinephrine are related to carcinogenesis and tumor progression (Mancino et al, 2011). In addition, there is a close relationship between immune and nervous systems.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These types of events occur due to secretion of catecholamines (stress-mediators) which increases in response to stressful events (Ganguly, 2010;Beaulieu and Gainetdinov, 2011). Most of catecholamines including epinephrine and norepinephrine are related to carcinogenesis and tumor progression (Mancino et al, 2011). In addition, there is a close relationship between immune and nervous systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated that mental and physiological conditions of individuals are important in the promotion and development of cancers and changes in patient's life style could be effective in incidence of stress (Cohen et al, 2007;Mancino et al, 2011;Barik et al, 2013). Cancer cells and nerve fibers have cross-talks and thus could influence on each other.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations